Effectiveness of inspiratory muscle training on respiratory fitness and breathlessness in chronic renal failure: A randomized control trial. (14th September 2020) - Yuenyongchaiwat, Kornanong; Namdang, Phuwarin; Vasinsarunkul, Phatsara; Phongsukree, Phoomipat; Chaturattanachaiyaporn, Kodchaphan; Pairojkittrakul, Sasipim; Traitanon, Opas
Abstract: Background: People with chronic renal failure (CRF) show decreased respiratory fitness and poor quality of life (QOL). Exercise during hemodialysis has been suggested to improve the cardio‐respiratory fitness. However, results of effects of respiratory muscle (RM) training on respiratory fitness and QOL are inconsistent. In addition, very few studies explored the association between inspiratory muscle (IM) training and sensation of breathlessness. Objectives: To examine the effects of IM training in hemodialysis patients on respiratory fitness QOL and breathlessness. Method: A randomized control trial with 50 CRF, who underwent hemodialysis (25 individuals in each group; IM training and sham group) was designed. Pulmonary function, RM strength, QOL (measured by Kidney Disease Quality of Life‐36), and sensation of breathlessness were measured before and after an 8‐week intervention. Results: Compared to the sham group, the IM strength increased in the intervention group after an 8‐week program (Δ25.92 ± 8.73 cmH2 O, p = 0.005). Significantly increased IM and forced vital capacity values in training groups was observed after an 8‐week intervention (Δ12.44 ± 3.07 cmH2 O and Δ0.097 ± 0.046 L, respectively), but not the sham group. Neither, the training group, nor the sham group were significantly different in the QOL. However, feeling of shortness of breath improved after the training program among inspiratory muscle training group, but not the sham group. Conclusion: IM training during hemodialysis could lead to an improvement of respiratory fitness and reduce breathlessness in people with CRF who are receiving hemodialysis. However, QOL was not different after the training program. The study suggests that after 8‐week intervention program, IM training (loading exercise) could improve IM strength, pulmonary function without any complications during the intervention program within 1–2 h.